The Layout of the Statistical Forecasts Regarding the Fight Against of the Chaos’s Vectors from the Space Geometry of the Illegal Drugs - Gabriela OPAIT (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2023)
The people’s life is actually in jeopardy due to the illicit drugs, because these influence variously the brain functions, heart or other organs. The persons who take illicit drugs can fall ill them mental state and thus they can manifest a whole range of mental ills. The people due to the effects of the illicit drugs can spoil or in other words they can alter them brain functions and as a consequence, they can display various emotions, as well as slowed down movements of the bodies. The persons due to the effect of the cocaine and heroin have an accelerated energy which produces energizing effects, unlike the cannabis and ecstasy which affect the vision and the feels.